ENVIRONMENTAL-BASED STUDENT WORKSHEETS DESIGN FOR ECONOMICSS SUBJECTS IN SENIOR HIGH SCHOOL - Yopi Nisa Febianti; Meli Nurkholis (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2022)
This study aims to identify the activities of the tofu and tempeh industry that can be used as a source of economics learning in senior high school, and how the design of environmental-based student worksheets. This study uses a qualitative method that is carried out on tofu and tempeh craftsmen in Cisambeng Village, Majalengka Regency. The subjects in this study were the community of tofu and tempeh craftsmen. The data collection techniques in this study are participatory observation, in-depth interviews, documentation, also interview instruments, observation instruments, recordings, and cameras are used. The data analysis technique in this study uses the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that various economics activities can be found in the tofu and tempeh industry in Cisambeng Village, Majalengka Regency which can be used as learning resources in economics subjects in senior high school. Suggestions for other researchers are to be able to continue this research in terms of utilizing environmental-based learning resources in the form of Students’ worksheets in order to assist in the process of learning economics